Decreased levels of nucleotide pyrophosphatase phosphodiesterase 1 are associated with cartilage calcification in osteoarthritis and trigger osteoarthritic changes in mice. Issue 7 (17th April 2012) - Bertrand, J; Nitschke, Y; Fuerst, M; Hermann, S; Schäfers, M; Sherwood, J; Nalesso, G; Ruether, W; Rutsch, F; Dell'Accio, F; Pap, T
Abstract : Objective: To analyse the function of nucleotide pyrophosphatase phosphodiesterase (NPP1), a member of the pyrophosphate pathway, in osteoarthritis (OA). Methods: mRNA expression of NPP1, ANK ankylosing protein and tissue non-specific alkaline phosphatase was assessed by quantitative PCR. NPP1 protein levels were analysed in mouse and human cartilage samples. Bone metabolism was analysed by F18-positron emission tomography-scanning and µCT in ttw/ttw mice. Ttw/ttw mice are mice carrying a loss-of-function mutation in NPP1. Calcification of articular cartilage was assessed using von Kossa staining and OA severity using the Mankin score. Cartilage remodelling was investigated by type X collagen immunohistochemistry. Results: Expression of NPP1, but not the other members of this pathway, inversely correlated with cartilage calcification and OA severity in mouse and humans. Proinflammatory cytokines downregulated the expression of NPP1, demonstrating an influence of inflammation on matrix calcification. Ttw/ttw mutant mice, carrying a loss-of-function mutation in NPP1, exhibit increased bone formation process in joints compared with wild types. Ttw/ttw mice also developed spontaneous OA-like changes, evaluated by histological analysis and in vivo imaging. Ectopic calcifications were associated with increased expression of collagen X in the cartilage. Conclusion: The authors conclude that OA is characterised by the reactivation of molecular signalling cascades involving proinflammatory cytokines, thereby regulating the pyrophosphate pathway which consequently leads to cartilage ossification, at least in part resembling endochondral ossification.